APLIKASI E-LEARNING PADA STMIK KHARISMA MAKASSAR - Alberthina Mual (STMIK KHARISMA Makassar, 2015)
This study aims to build e-Learning applications at STMIK Kharisma Makassar and evaluate the applications being built. Data collection in this study was carried out using library techniques, then data were analyzed using qualitative methods. The system is designed using Data Flow Diagrams (DFD), Database Design, and Input / Output and is implemented into the PHP programming language and MySQL database. For testing the system used the white box and black box methods. The elearning application program makes it easier for students and lecturers in the teaching and learning process. Evaluation shows that with this program students can read / retrieve material, assignments and articles provided by lecturers from courses that are programmed